2019
DOI: 10.1111/jch.13610
|View full text |Cite
|
Sign up to set email alerts
|

Difference in 24‐hour urine sodium excretion between controlled and uncontrolled patients on antihypertensive drug treatment

Abstract: The objective of this study was to evaluate the association between sodium intake and blood pressure (BP) control in hypertensive patients taking antihypertensive medications by using 24‐hour urine collection and 24‐hour ambulatory BP. This is a cross‐sectional community‐based study and conducted in 2011 and 2012. A total of 1128 participants were recruited from five cities in Korea. Among them, 740 participants who had complete 24‐hour urine collection and valid 24‐hour ambulatory BP data were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies assessed for eligibility were meta‐analyses (n = 3), prospective cohort studies (n = 10), cross‐sectional studies (n = 9), post hoc analyses of RCT’s (n = 1), quasi‐experimental studies (n = 2), and modeling analyses (n = 2). Three studies assessed mortality outcomes, 22‐24 six studies assessed morbidity outcomes, 25‐30 15 studies assessed clinically relevant surrogate outcomes, 31‐45 including 12 that assessed blood pressure outcomes, 31‐34,38‐45 and three studies assessed physiologic outcomes 46‐48 . Of these studies, only two met the minimum methodological criteria for detailed critical appraisal (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Studies assessed for eligibility were meta‐analyses (n = 3), prospective cohort studies (n = 10), cross‐sectional studies (n = 9), post hoc analyses of RCT’s (n = 1), quasi‐experimental studies (n = 2), and modeling analyses (n = 2). Three studies assessed mortality outcomes, 22‐24 six studies assessed morbidity outcomes, 25‐30 15 studies assessed clinically relevant surrogate outcomes, 31‐45 including 12 that assessed blood pressure outcomes, 31‐34,38‐45 and three studies assessed physiologic outcomes 46‐48 . Of these studies, only two met the minimum methodological criteria for detailed critical appraisal (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for participant recruitment and the measurement protocols have been described in detail elsewhere [ 6 , 7 ]. The original study was designed to evaluate the association between salt intake and BP.…”
Section: Methodsmentioning
confidence: 99%
“…Higher sodium intake is also associated with elevated BP 40 , 41 , 42 and may be related to decreased efficacy of antihypertensive medication. 43 We observed that the 24‐hour urine sodium excretion was similar between groups and tended to be lower in the BP‐difficult group (Table 1 ), suggesting that difficulty in lowering BP was not attributed to higher sodium intake. Lastly, the groups had similar estimated glomerular filtration rates and essentially no proteinuria (24‐hour urine protein:creatinine ratio of 0.12), which excludes differences in kidney function or glomerular damage as causes for the observed differential gene expression.…”
Section: Discussionmentioning
confidence: 69%